Progress in Spatial Data Handling 12th International Symposium on Spatial Data Handling - Riedl, Andreas; Kainz, Wolfgang; Elmes, Gregory A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
The series of International Symposia on Spatial Data Handling started in Zurich, Switzerland, in 1984. Since then it has evolved into a biennial event of high calibre, at which recent trends and developments in geographic information science are discussed. The proceedings of this series have become an important reference for researchers and students in the field of geography, cartography, and geoinformation.
Plenary of Submitted Papers -- The Devil is still in the Data: Persistent Spatial Data Handling Challenges in Grassroots GIS -- Physical vs. Web Space Similarities and Differences -- Spatial Cognition -- Utilization of Qualitative Spatial Reasoning in Geographic Information Systems -- Identification of the Initial Entity in Granular Route Directions -- Data Models -- Modeling and Engineering Algorithms for Mobile Data -- Database Model and Algebra for Complex and Heterogeneous Spatial Entities -- QACHE: Query Caching in Location-Based Services -- A Voronoi-Based Map Algebra -- Modeling Geometric Rules in Object Based Models: An XML / GML Approach -- Data Mining -- Exploring Geographical Data with Spatio-Visual Data Mining -- Continuous Wavelet Transformations for Hyperspectral Feature Detection -- Measuring Linear Complexity with Wavelets -- Expert Knowledge and Embedded Knowledge: Or Why Long Rambling Class Descriptions are Useful -- Data Retrieval -- Preference Based Retrieval of Information Elements -- Spatiotemporal Event Detection and Analysis over Multiple Granularities -- Reduced Data Model for Storing and Retrieving Geographic Data -- Filling the Gaps in Keyword-Based Query Expansion for Geodata Retrieval -- Data Quality -- Using Metadata to Link Uncertainty and Data Quality Assessments -- An Evaluation Method for Determining Map-Quality -- Efficient Evaluation Techniques for Topological Predicates on Complex Regions -- Implementation of a Prototype Toolbox for Communicating Spatial Data Quality and Uncertainty Using a Wildfire Risk Example -- Integration and Fusion -- Changes in Topological Relations when Splitting and Merging Regions -- Integrating 2D Topographic Vector Data with a Digital Terrain Model a Consistent and Semantically Correct Approach -- A Hierarchical Approach to the Line-Line Topological Relations -- Coastline Matching Process Based on the Discrete Fréchet Distance -- Semantics and Ontologies -- Characterizing Land Cover Structure with Semantic Variograms -- Semantic Similarity Measures within the Semantic Framework of the Universal Ontology of Geographical Space -- A Quantitative Similarity Measure for Maps -- A Semantic-based Approach to the Representation of Network-Constrained Trajectory Data -- Towards an Ontologically-driven GIS to Characterize Spatial Data Uncertainty -- 2D-Visualization -- Structuring Kinetic Maps -- Advanced Operations for Maps in Spatial Databases -- A Tangible Augmented Reality Interface to Tiled Street Maps and its Usability Testing -- A Linear Programming Approach to Rectangular Cartograms -- 3D-Visualization -- Automated Construction of Urban Terrain Models -- A Flexible, Extensible Object Oriented Real-time Near Photorealistic Visualization System: The System Framework Design -- A Tetrahedronized Irregular Network Based DBMS Approach for 3D Topographic Data Modeling -- 3D Analysis with High-Level Primitives: A Crystallographic Approach -- Generalization -- The Hierarchical Watershed Partitioning and Data Simplification of River Network -- Grid Typification -- Skeleton Based Contour Line Generalization -- Conflict Identification and Representation for Roads Based on a Skeleton -- The stroke Concept in Geographic Network Generalization and Analysis -- Uncertainty -- An Integrated Cloud Model for Measurement Errors and Fuzziness -- The Influence of Uncertainty Visualization on Decision Making: An Empirical Evaluation -- Modeling Uncertainty in Knowledge Discovery for Classifying Geographic Entities with Fuzzy Boundaries -- Capturing and Representing Conceptualization Uncertainty Interactively using Object-Fields -- Elevation Modeling -- From Point Cloud to Grid DEM: A Scalable Approach -- Use of Plan Curvature Variations for the Identification of Ridges and Channels on DEM -- An Evaluation of Spatial Interpolation Accuracy of Elevation Data -- Working with Elevation -- I/O-Efficient Hierarchical Watershed Decomposition of Grid Terrain Models -- Tradeoffs when Multiple Observer Siting on Large Terrain Cells -- Scale-Dependent Definitions of Gradient and Aspect and their Computation -- Spatial Modeling -- Development Density-Based Optimization Modeling of Sustainable Land Use Patterns -- Building an Integrated Cadastral Fabric for Higher Resolution Socioeconomic Spatial Data Analysis -- Analysis of Cross Country Trafficability.
Keywords: Earth sciences; Environmental sciences; Computers; Geographical information systems; Regional planning; Urban planning; Earth Sciences; Environmental Science and Engineering; Geographical Information Systems/Cartography.; Earth Sciences, general; Math. Appl. in Environmental Science; Landscape/Regional and Urban Planning; Information Systems and Communication Service; Electronic books